2024
DOI: 10.1021/acsomega.3c04427
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electronic Interactions within the Pd-CeO2/Carbon Onions Define the Efficient Electrocatalytic Ethanol Oxidation Reaction in Alkaline Electrolytes

Jimodo J. Ogada,
Tobechukwu J. Ehirim,
Adewale K. Ipadeola
et al.

Abstract: Porous Pd-based electrocatalysts are promising materials for alkaline direct ethanol fuel cells (ADEFCs) and ethanol sensors in the development of renewable energy and point-of-contact ethanol sensor test kits for drunk drivers. However, experimental and theoretical investigations of the interfacial interaction among Pd nanocrystals on supports (i.e., carbon black (CB), onion-like carbon (OLC), and CeO 2 /OLC) toward ADEFC and ethanol sensors are not yet reported. This is based on the preparation of Pd-CeO 2 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Optimizing the utilization of palladium atoms is at the forefront of current research endeavors . Several methods have been developed to precisely control the morphology, scale, structure, and composition of palladium (Pd)-based nanocatalysts to enhance their catalytic performance. Several studies have shown that adding a second or third metallic element (M 1 and M 2 ) to palladium-based binary (PdM) or ternary (PdM 1 M 2 ) alloys significantly increases the reaction rates of oxygen reduction reactions (ORR) and alcohol oxidation reactions (AOR). , For instance, a series of porous palladium- and platinum-based alloys were synthesized and exhibited exceptional electrocatalytic properties. Highly efficient electrode catalysts with ultra-low Pt loadings were obtained by depositing Pt on three-dimensional hydroxylated Ti 3 C 2 T x MXene nanonet or porous carbon substrates. Alloying processes refine the catalyst’s morphology and electronic configuration, thereby elevating its catalytic efficiency and resistance to poisoning during ethanol oxidation reactions. , The optimized morphology typically contains numerous nanopores and a large specific surface area. Such enhancement can substantially augment ion transport within the nanostructures, thereby offering an abundance of active sites on lattice planes for the catalysis of ethanol oxidation. , Furthermore, the optimized electronic structure enhances KOH/C 2 H 5 OH adsorption and electron transfer during the reaction process, resulting in an improved recovery rate.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the utilization of palladium atoms is at the forefront of current research endeavors . Several methods have been developed to precisely control the morphology, scale, structure, and composition of palladium (Pd)-based nanocatalysts to enhance their catalytic performance. Several studies have shown that adding a second or third metallic element (M 1 and M 2 ) to palladium-based binary (PdM) or ternary (PdM 1 M 2 ) alloys significantly increases the reaction rates of oxygen reduction reactions (ORR) and alcohol oxidation reactions (AOR). , For instance, a series of porous palladium- and platinum-based alloys were synthesized and exhibited exceptional electrocatalytic properties. Highly efficient electrode catalysts with ultra-low Pt loadings were obtained by depositing Pt on three-dimensional hydroxylated Ti 3 C 2 T x MXene nanonet or porous carbon substrates. Alloying processes refine the catalyst’s morphology and electronic configuration, thereby elevating its catalytic efficiency and resistance to poisoning during ethanol oxidation reactions. , The optimized morphology typically contains numerous nanopores and a large specific surface area. Such enhancement can substantially augment ion transport within the nanostructures, thereby offering an abundance of active sites on lattice planes for the catalysis of ethanol oxidation. , Furthermore, the optimized electronic structure enhances KOH/C 2 H 5 OH adsorption and electron transfer during the reaction process, resulting in an improved recovery rate.…”
Section: Introductionmentioning
confidence: 99%